HUBUNGAN TUGAS KESEHATAN KELUARGA DENGAN MANAJEMEN DIRI KLIEN HIPERTENSI DI PUSKESMAS SILO 1 KABUPATEN JEMBER: The Relationship of Family Health Tasks and Self-Management of Hypertension Clients at Silo 1 Health Center Jember District - Arsita, Angelica Shafabila; A, Sri Wahyuni; Asmuji (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
The role of the family is very important in carrying out family health duties for family members who carry out hypertension self-management. Apart from the family, the role of health workers is to carry out strategies for pharmacological and non-pharmacological treatment. The Health Promotion model is a non-pharmacological strategy that must be implemented by health workers. This research is to determine the relationship between family health tasks and self-management of hypertensive clients at the Silo 1 Health Center, Jember Regency. This research design uses a correlational cross sectional approach, the population is 454 hypertensive clients, the size used is 213 hypertensive clients, the sampling technique uses simple random sampling, data analysis uses the Spearman Rank test. Tested using the family health task questionnaire and HSMBQ. Based on the research results, most of the family health tasks were in the quite good category, numbering 159 people (74.7%) while hypertensive clients who had quite good self-management were 172 respondents (80%). Analysis of the relationship between family health tasks and self-management resulted in a p value = 0.012 with r = 0.172 so that H0 was rejected, which means there is a significant relationship between family health tasks and self-management of hypertensive clients. The results of this study can be a basis for health workers, especially those who focus on hypertension health problems, to make efforts to improve health promotion.